A path to resilience and social integration: motivations of international student volunteers during the COVID-19 lockdown in Wuhan - Meraj Malakouti; Asma Khaleel Abdallah; Ahmed Alkaabi (Frontiers in Psychology)
IntroductionThe coronavirus disease 2019 (COVID-19) epidemic emerged globally, resulting in the shutdown of schools and universities. The January 2020 lockdown in Wuhan, China, profoundly impacted residents’ daily lives, particularly international students who faced restrictions within their campuses and dormitories. This qualitative study aimed to investigate the motivations of international student volunteers during Wuhan’s COVID-19 lockdown and identify how this voluntary activity fostered resilience and social integration among them.MethodsThe study adopts a qualitative approach using semi-structured in-depth interviews with 14 international PhD students at a university in China who volunteered during the three-month Wuhan lockdown. Data saturation was achieved through purposeful sampling. Data were transcribed, and thematic analysis was applied, with coding using NVivo 14.ResultsAfter applying thematic analysis, three key themes were identified: (a) motivation for volunteering, (b) resilience through volunteering, and (c) social integration and community bonding through volunteering. These themes were explored in relation to the psychological needs defined in Self-Determination Theory.DiscussionOur findings further indicate that coping via volunteering not only enhanced psychological resilience but also significantly facilitated social connections among culturally diverse groups. These findings highlight the importance of understanding volunteer motivations and experiences, providing valuable insights for universities and policymakers to develop strategies that enhance student support and community resilience during a crisis.